2011
DOI: 10.1111/j.1755-263x.2011.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Promise and problems for estimating management costs of marine protected areas

Abstract: Management costs are rarely taken into account in marine protected area (MPA) design. We estimate the management costs of two different protection scenarios within a large proposed MPA, the Coral Sea in Australia. We use three methods to estimate costs: an existing model of global MPA management costs; a new statistical model based on Australian MPA management costs; and expert estimates that extrapolate from the adjacent Great Barrier Reef Marine Park. Both the new statistical model and expert estimates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 18 publications
0
56
1
Order By: Relevance
“…Only a few studies have explicitly quantified these costs (Ban and Klein 2009;Davis et al 2015). Ban et al (2011) compared the enforcement costs for staffing an entirely no-take protected area versus a mixed zone seascape (protected and fished) and found that compliance staffing was doubled when mixed zoning occurred.…”
Section: Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few studies have explicitly quantified these costs (Ban and Klein 2009;Davis et al 2015). Ban et al (2011) compared the enforcement costs for staffing an entirely no-take protected area versus a mixed zone seascape (protected and fished) and found that compliance staffing was doubled when mixed zoning occurred.…”
Section: Costsmentioning
confidence: 99%
“…Despite being critical to decision-making about natural resource management (Naidoo et al 2006), costs associated with establishing and managing protected areas are often poorly reported, difficult to quantify (Balmford et al 2004;Ban et al 2011), and highly contextual (Rojas-Nazar et al 2015). As a flexible way to integrate the amalgam of costs (e.g., stock assessments, ecological monitoring, staffing, enforcement, etc.)…”
Section: Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, compliance levels mostly dependent on enforcement require a strong authority presence, which translates into high operation costs (Keane et al 2008, Ban et al 2011. The high awareness level related to fines may be caused by government efforts to educate for compliance, which at the time of this study emphasized the illegality of fishing in no-take zones.…”
Section: Discussionmentioning
confidence: 99%
“…We used the maximum possible salary so as not to underestimate the budget. We assumed that patrols were always carried out by two rangers and that staff on-costs were 25% (Ban et al, 2011).…”
Section: Enforcement Costmentioning
confidence: 99%